Christian reflections on the leadership challenge - Kouzes, James M., 1945-; Posner, Barry Z.; Kouzes, James M., 1945- (San Francisco, CA : Jossey-Bass, 2004)
For Christian leaders in any organization, ministry, or endeavor, this book provides a faith-based companion to The Leadership Challenge, the #1 bestselling leadership book of all time.
Leadership is everyone's business / James M. Kouzes and Barry Z. Posner -- The five practices of exemplary leadership / James M. Kouzes and Barry Z. Posner -- Part 1 : model the way -- Reflections on model the way / John C. Maxwell -- Part 2: inspire a shared vision -- Reflections on inspire a shared vision / David McAllister-Wilson -- Part 3: challenge the process -- Reflections on challenge the process / Patrick Lencioni -- Part 4: enable others to act -- Reflections on enable others to act / Nancy Ortberg -- Part 5: encourage the heart -- Reflections on encourage the heart / Ken Blanchard -- Leadership is a relationship / James M. Kouzes and Barry Z. Posner.
Includes bibliographical references (p. 127-129) and index.
Keywords: Leadership -- Religious aspects -- Christianity